Consolidation treatment of durvalumab after chemoradiation in real‐world patients with stage III unresectable non‐small cell lung cancer. Issue 6 (13th April 2020) - Chu, Chia‐Hsun; Chiu, Tzu‐Hsuan; Wang, Chin‐Chou; Chang, Wen‐Chen; Huang, Allen Chung‐Cheng; Liu, Chien‐Ying; Wang, Chih‐Liang; Ko, Ho‐Wen; Chung, Fu‐Tsai; Hsu, Ping‐Chih; Guo, Yi‐Ke; Kuo, Chih‐Hsi S.; et al.
Abstract : Background: Treatment for stage III non‐small cell lung cancer (NSCLC) of unresectable disease mainly involves concurrent chemoradiation (CRT). Post‐CRT consolidation treatment with durvalumab is a major therapeutic advance that provides survival benefit in this group of patients. However, the performance of this treatment strategy remains to be studied in a real‐world setting. Methods: A total of 31 patients who had disease control post‐CRT were included in the durvalumab early access program (EAP) as an intent‐to‐treat cohort and retrospectively reviewed for post‐CRT progression‐free survival (PFS) and time to metastatic disease or death (TMDD). The neutrophil‐to‐lymphocyte ratio (NLR) at the initiation of durvalumab was analyzed in 29 patients. Results: The median time from the completion of concurrent CRT to the initiation of durvalumb was 2.8 months. The objective response was 25.8% and the 12 month PFS and TMDD‐free rate were 56.4% and 66.9%, respectively. The low NLR patients showed a significantly longer post‐CRT PFS (not reach vs. 12.0 months [95% CI: 5.5–not estimable]; P = 0.040; the hazard ratio for disease progression or death, 0.23 [95% CI: 0.05–1.00]; P = 0.048) and the 12 month post‐CRT PFS rate (82.5 vs. 42.6%). The post‐CRT TMDD (not reach vs. 12.6 months, [95% CI: 10.8–not estimable]; P = 0.010; the hazard ratio for distant metastasis or death, 0.11 [95% CI: 0.01–0.88]; P = 0.037) and 12 month post‐CRT TMDD‐free rate (90.9 vs. 57.1%) were also significantly higher in the low NLR patients. Conclusions: Durvalumab consolidation treatment in real‐world patients showed substantial efficacy and the correlation with the NLR level warrants further investigation.